(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, in the course of our research, the problematic study conditions of adolescence in the period of destructive behavior, the relevance of their thoughts and opinions have been scientifically substantiated. Adolescence during destructive behavior appearances psychological diagnosis and correction topic theoretical and practical in terms of current has been problems in the end enters.